Particulate Matter Monitoring and Assessment through Internet of Things: a Health Information System for Enhanced Living Environments. - Marques, Gonçalo; Pitarma, Rui (Journal of Medical Systems, 2020)
People spend most of their time inside buildings. Therefore, indoor air quality monitoring contributes to improve health and well-being. Several studies focus on the critical impact of particulate matter on residential air quality. In 2016, particulate matter caused 412 thousand premature deaths in 41 European countries. This paper presents the development of an affordable health information system for enhanced living environments. The authors propose a cost-effective, modular, scalable, and easy installation solution for particulate matter monitoring. The system is connected to ThingSpeak. It can be installed in any type of building. It requires only a power source and a Wi-Fi network with internet access. The main contribution of this paper is to present the detailed architecture and testing results. The particulate matter monitoring system was installed for one week in a domestic kitchen with an open fireplace. The results showed impact of the biomass burning on indoor air quality. The mean values per day ranged from: 10.53 to 50.62 μg/m3 for PM1.0, 15.35 to 69.37 μg/m3 for PM2.5, and 20.1 to 90.69 μg/m3 for PM10. The maximum values per hour were registered at 13:00: 72.14 μg/m3 for PM1.0, 99.70 μg/m3 for PM2.5, and 132.13 μg/m3 for PM10. Cost-effective sensors do not have the accuracy level of industrial equipment. Therefore, they should not be used for numerical and in-depth accurate characterization of the environment. Nevertheless, continuous particulate matter monitoring provides consistent data series for analysis of indoor air quality evolution.